2010
DOI: 10.1128/jvi.00189-10
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Specific Interaction of UL112-113 p84 with UL44 DNA Polymerase Processivity Factor in Promoting DNA Replication of Human Cytomegalovirus

Abstract: The human cytomegalovirus (HCMV) UL112-113 region encodes four phosphoproteins with common amino termini (p34, p43, p50, and p84) via alternative splicing and is thought to be required for efficient viral DNA replication. We have previously shown that interactions among the four UL112-113 proteins regulate their intranuclear targeting and enable the recruitment of the UL44 DNA polymerase processivity factor to viral prereplication foci. Here, we show that in virus-infected cells, the UL112-113 proteins form a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 45 publications
(56 reference statements)
3
48
2
1
Order By: Relevance
“…The role of the association of these proteins within infected cells remains unknown. Recently, it has been reported that UL44 and UL84 are part of protein complex in infected cells that also contains the viral proteins IE2-86 and UL112-113(p84) (28). Thus, either IE2 or UL112-113(p84) might also bridge the association of UL44 and UL84 in infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the association of these proteins within infected cells remains unknown. Recently, it has been reported that UL44 and UL84 are part of protein complex in infected cells that also contains the viral proteins IE2-86 and UL112-113(p84) (28). Thus, either IE2 or UL112-113(p84) might also bridge the association of UL44 and UL84 in infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…UL112-113 encodes four phosphoproteins, which are supposed to recruit proteins involved in DNA replication, to viral RCs (128,131). These viral replication core proteins include the DNA polymerase UL54, the polymerase-associated processivity factor UL44, and the ssDNA binding protein UL57, as well as a heterotrimer consisting of the DNA helicase UL105, the primase UL70, and the primase-associated factor (132,133).…”
Section: Nuclear Dna Virus Replication Centersmentioning
confidence: 99%
“…IE2-p86 recruits DE proteins encoded by UL112-113 to specialized nuclear sites (18,19), which in turn recruits ppUL84 and ppUL44, the viral DNA Pol processivity (Proc) factor, forming a complex that recognizes the origin of viral DNA replication, oriLyt, to initiate DNA synthesis (20)(21)(22)(23). The IE2-p86/ppUL84/ ppUL44/UL112-113 protein complex recruits single-stranded DNA binding protein, DNA Pol, and helicase-primase (22,23), ensuring timely production of viral DNA starting about 24 h postinfection (hpi) and peaking at 48 hpi. Viral DNA is packaged into preformed capsids starting at 48 hpi and peaking at 72 to 96 hpi (1).…”
mentioning
confidence: 99%